Reconstruction of Artificial Intelligence Ethics in Tariq Ramadan's Perspective - Wiwudha, Nayaka Inabhimantra; Bahri, Q'dham Zainal; Mutya, Pashya Nanda (Journal of Islamic Thought and Philosophy, 2024)
This research discusses AI Ethics, which arises from the rapid development of AI that creates various problems. Meanwhile, Tariq Ramadan's Ethical Concept, based on Maqashid Asy-Syari'ah, has pluralistic and inclusive values. This ethic becomes a new perspective that can be applied to AI. This research uses a qualitative approach with the library research method (literature sources). The research results show that AI is the ability of computational systems to perform tasks of human intelligence. AI was initially designed to resemble human intelligence as closely as possible, even to match it. AI has the potential to threaten human sustainability when it reaches the stage of superintelligence. The concept of friendly AI can reduce the risk of human extinction. The application of Ramadan's Ethics, based on Maqashid Asy-Syari'ah, which integrates socio-cultural and religious aspects, offers an AI ethics concept to be applied according to the context in which AI is needed. The framework of friendly AI proposed by Ramadan has its own uniqueness compared to Asimov's Laws, Yudkowsky's Utility, and social-friendly AI.